PENGEMBANGAN MODUL KALKULUS TERINTEGRASI STRATEGI PEMBELAJARAN TWO STAY TWO STRAY BERBANTUAN MEDIA KARTU UNTUK PEMBELAJARAN DI PERGURUAN TINGGI SWASTA KOMPUTER DI KOTA PADANG - ulhusna, mishbah (journal of residu, 2019)
This research is motivated by learning that is still teacher-centered. This study aims to produce an integrated module of learning strategies Two Stay Two Stray with card media assisted to increase the participation and activeness of students in learning. This type of research is a development research with an IDI model. The conclusion of this research is at the stage of validity obtaining an average 84,33% with very valid criteria, in the practical stage, get results 79% with practical criteria, and at the effectiveness stage using statistical analysis, namely equations Paired Sample Test with result sig (2.tailed) 0,003 value α 0,05 this means that there are differences in student calculus learning outcomes between before and after being given an integrated strategy module Stay Two Stray.